HARNESSING TECHNOLOGY FOR EFFECTIVE SCIENCE TEACHING PEDAGOGIES IN HIGHER INSTITUTIONS IN NIGERIA IN AN ERA OF INSECURITY AND ECONOMIC MELTDOWN. (UNIZIK Journal of STM Education, 2025)
The study investigated Harnessing Technology for Effective Science Teaching Pedagogies in Higher Institutions of Learning in Nigerian in an era of Insecurity and Economic Meltdown. This is a descriptive survey study. The study was carried out in Nnamdi Azikiwe University Awka, South East Nigeria.  To guide the research, three questions were formulated by the researchers. The population of the study comprises of all teaching staff members from faculty of education Nnamdi Azikiwe University Awka. A simple random sampling technique was used to select 125 teaching staff from Science Education, Health Education and Human Kinetics departments in Faculty of Education at Nnamdi Azikiwe University Awka for the study. Data collection was done using a validated questionnaire instruments on Harnessing Technology for Effective Science Teaching Pedagogies in Higher Institutions in an era of Insecurity and Economic Meltdown (HTESTPHILEIEM), consisting of 25 items which were distributed and were collected on the spot to ensure that the instruments returned completely. The reliability index was determined by administering the questionnaire to 20 teaching staff from the science education, Health Education and Human Kinetics department in faculty of Education at Chukwuemeka Odumegwu Ojukwu University, yielding an impressive coefficient of 0.86 through Cronbach Alpha technique coefficient analysis. Mean and standard deviation was used to answers the research questions. The findings of this study showed established that technology-enhanced pedagogies for science teaching in higher institutions of learning were effective, infrastructural requirements are needed for the successful integration of technology-enhanced pedagogies into science teaching in higher institutions of learning and,  that educator support is needed for successful integration of technology-enhanced pedagogies into science teaching in higher institutions of learning in an era of insecurity and economic meltdown. Based on the findings, recommendations were made among which are that higher institution in Nigeria should endeavour to have technological infrastructures and facilitate regular training of teachers on the effective ways of integrating technology for effective science teaching pedagogies in our institutions of learning in the best interest of our nation and our students in particular.
Keywords: Harnessing, Technology, Effective Science Teaching, Pedagogies, era of insecurity and economic meltdown